An Attentional Goldilocks Effect: An Optimal Amount of Social Interactivity Promotes Word Learning From Video. Issue 1 (1st January 2016) - Nussenbaum, Kate; Amso, Dima
Abstract : Television can be a powerful education tool; however, content makers must understand the factors that engage attention and promote learning from screen media. Prior research has suggested that social engagement is critical for learning and that interactivity may enhance the educational quality of children's media. The present study examined the effects of increasing the social interactivity of television on children's visual attention and word learning. Three- to 5-year-old ( M age = 4;5, SD = 9 months) children completed a task in which they viewed videos of an actress teaching them the Swahili label for an on-screen image. Each child viewed these video clips in 4 conditions that parametrically manipulated social engagement and interactivity. We then tested whether each child had successfully learned the Swahili labels. Though 5-year-old children were able to learn words in all conditions, we found that there was an optimal level of social engagement that best supported learning for all participants, defined by engaging the child but not distracting from word labeling. Our eye-tracking data indicated that children in this condition spent more time looking at the target image and less time looking at the actress's face as compared with the most interactive condition. These findings suggest that social interactivity is critical to engaging attention and promoting learning from screen media up until a certain point, after which social stimuli may draw attention away from target images and impair children's word learning.